Cystic fluid neutrophil gelatinase-associated lipocalin (NGAL) concentration in differential diagnosis of pancreatic cystic lesions: a new factor enters the scene? - Lipinski, Michal; Degowska, Malgorzata; Rydzewska, Grazyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2018)
Introduction : Neutrophil gelatinase-associated lipocalin – 25 kDa peptide – is at present one of the most fascinating and unrecognised proteins implicated in the process of tumour development. Precise assessment of pancreatic cystic lesions is crucial for selecting available treatment options, such as conservative therapy or surgical resection. Aim : To determine the utility of NGAL concentration in cyst fluid obtained by endoscopic ultrasound (EUS) with EUS-guided fine-needle aspiration (EUS-FNA) to distinguish neoplastic pancreatic cysts from pseudocysts. Material and methods: Twenty-two patients underwent EUS and FNA of a pancreatic cystic lesion; 9 of these patients underwent surgical resection, providing a histologic diagnosis of the cystic lesion. Furthermore, the final diagnosis was based on cyst fluid cytology, cyst fluid tumour markers (CEA, CA 72-4, CA 19-9), and medical history. Patients were divided in two groups: cystic neoplasms and inflammatory cysts (pseudocysts). Results : The final diagnosis was pseudocyst in 7 patients, serous cystadenoma in 4, mucinous cystadenoma in 3, intraductal papillary mucinous neoplasms in 6 patients, and cystic form of pancreatic adenocarcinoma in 2. Cyst fluid analysis of these patients showed that median cyst fluid NGAL for the cystic neoplasm group (211 ng/ml; n = 15) was significantly lower (p = 0.02) than the inflammatory cystic group (4689 ng/ml; n = 7). Correlation analysis showed that only fluid CA 72-4 was positively related to NGAL (r = 0.8, p < 0.01). Conclusions : In this single-centre study, pancreatic cyst fluid NGAL concentration appeared to be useful in distinguishing neoplastic pancreatic cysts from pseudocysts. Larger studies are recommended to evaluate this role further.